Kimaragang folklore game app development: ‘e’ gadung’ - Lilian Lee Shiau Gee; Victor B. Pangayan; Danial Kordmodanlou (Allied Business Academies, 2022)
Digital games have evolved as a crucial interactive media capable of encouraging and fostering cultural heritage through visualisations, with a special emphasis on preserving and maintaining Sabahan folklore for future generations. This paper discusses the development of the E'Gadung app as well as the outcomes of a study on Kimaragang ethic group preservation. A documentary analysis, prototyping, playtesting and semi-structured interview has been carried out. The results indicate that the digital game significantly increased the Kimaragang group's awareness of the importance of protecting local cultural heritage. Additionally, positive youth responses have shown that the game 'E' Gadung' has been successfully presented using a combination of artistic elements to educate younger generations, especially Kimarang ethnic children aware to their own culture and heritage. Thus, it is necessary to address "continuous process" digitalization strategies in order to preserve knowledge of intangible cultural resources, particularly Sabah's ethnic folklore.